RANCANGAN APLIKASI PENERIMAAN ANGGOTA UNIT KEGIATAN MAHASISWA (UKM) UNIVERSITAS BANTEN JAYA MENGGUNAKAN DESIGN THINKING MODEL - Dedi Juniansha; Mochamad Yusuf Romdoni (LPPM Unbaja, 2025)
Student Activity Units (UKM) are student organizations in universities that accommodate various student interests and talents outside of academic activities. UKM serves as a forum for students to develop themselves, channel hobbies, and improve various skills through extracurricular activities. The purpose of this research is to design and build an information system that can simplify the process of accepting cadres in an organization, especially student organizations. This system aims to increase efficiency, transparency, and accuracy in managing applicant data, as well as simplify the selection and recruitment process for UKM members. The presence of this application will be very helpful in serving the registration of every student who is interested in becoming a prospective member without having to visit each UKM and can reduce the cost of procuring paper and stationery as well as time and energy. This UKM member acceptance application will be built with web-based software and implemented online, where students can view information and the registration agenda and the selection schedule for each organization. In addition, each committee unit can monitor the progress of each prospective participant who registers and can also view the detailed profile of each prospective participant. This application was developed using the PHP programming language supported by the Bootstrap framework, which provides an excellent and flexible experience when accessed on today's smartphones. The system flow design uses the Unified Modeling Language (UML) and Design Thinking Model. This research uses a waterfall method approach in system development, and the results are expected to help every UKM administrator serve prospective participants more easily, effectively, and efficiently.